ANALYSIS OF THE ROLE OF WALI MUHAKKAM IN THE MARRIAGE LEGALIZATION (ISBAT NIKAH) CASE INVOLVING A PASTOR’S CHILD: A STUDY OF KARAWANG RELIGIOUS COURT DECISION NUMBER 248/PDT.P/2021/PA.KRW - Madaniy, Faruq Zakiy; Adang Darmawan Achmad; Hudzaifah Achmad Qotadah (Gapenas Publisher, 2024)
In Indonesia, marriage is regulated by positive law and religious principles, making it a social agreement and a sacred covenant imbued with spiritual dimensions. The Marriage Law highlights the significance of physical and emotional bonds as the foundation for building a prosperous and enduring family life, grounded in devotion to God Almighty. Within Islamic law and the Compilation of Islamic Law (KHI), the presence of a nasab guardian for the bride is a fundamental requirement for the marriage's validity. This guardian, typically a male relative from the bride's lineage, plays a crucial role in ensuring the legality of the union according to Islamic tenets. However, challenges may arise regarding the availability or presence of the nasab guardian. For instance, in the marriage between Sadam Husen bin Aji Sena and Dwi Yanthi Pranatalia Sipayung, the absence of the nasab guardian was due to religious differences within the bride's family. Other common issues include the guardian's refusal or inability to attend the marriage ceremony. In such cases, some individuals appoint a wali muhakkam, a guardian selected through community consensus or custom. However, the role of wali muhakkam has yet to be formally acknowledged in Indonesian marriage law. This study employs a qualitative approach with descriptive analysis to explore the isbat nikah case in the Karawang Religious Court (Decision No. 248/Pdt.P/2021/PA.Krw), which validated a marriage involving a wali muhakkam. Through interviews, observations, and document analysis, findings suggest that isbat nikah is often utilized to address nasab guardian issues, though its application should be carefully regulated to prevent misuse. Premarital education is recommended to enhance public awareness and ensure adherence to legal marriage procedures